2016
DOI: 10.1080/21645515.2017.1264748
|View full text |Cite
|
Sign up to set email alerts
|

Hymenoptera venom allergy in outdoor workers: Occupational exposure, clinical features and effects of allergen immunotherapy

Abstract: Objectives. To describe (i) the clinical characteristics of workers, exposed to hymenoptera stings, with an ascertained diagnosis of Hymenoptera Venom Allergy (HVA), (ii) the specific role of occupational exposure, (iii) the effect of Venom Immunotherapy (VIT) in reducing the severity of allergic episodes in workers exposed to repeated stings of hymenoptera, and (iv) the management of the occupational consequences caused by allergic reactions due to hymenoptera stings.Methods. Between 2000 and 2013 an observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In addition to beekeepers [13], for whom a specific risk is recognized, other workers such as foresters, farmers, gardeners, truck drivers, masons, and electricians [258,259] also experience systemic reactions more frequently, as do greenhouse workers, who are exposed to bumblebee stings [8,260]. For these categories, hymenoptera venom allergy can be considered an occupational disease [259,261] necessitating specific primary prevention measures [262]. Hymenoptera venom allergy is a recognized cause of work disability that can require a worker to change or leave his/her profession in order to reduce the risk of exposure [263].…”
Section: Professional Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to beekeepers [13], for whom a specific risk is recognized, other workers such as foresters, farmers, gardeners, truck drivers, masons, and electricians [258,259] also experience systemic reactions more frequently, as do greenhouse workers, who are exposed to bumblebee stings [8,260]. For these categories, hymenoptera venom allergy can be considered an occupational disease [259,261] necessitating specific primary prevention measures [262]. Hymenoptera venom allergy is a recognized cause of work disability that can require a worker to change or leave his/her profession in order to reduce the risk of exposure [263].…”
Section: Professional Aspectsmentioning
confidence: 99%
“…A recent Italian study conducted on 184 patients with anaphylactic reactions to hymenoptera venom showed an occupational cause in 17.4% of cases; of these, 71.8% continued to work after having received VIT. Re-stung workers (31.2%) were effectively protected [261]. The impact of VIT on professional activity increases with occupational risk [263].…”
Section: Professional Aspectsmentioning
confidence: 99%
“…Although different methods used for assessing sensitization make it difficult to compare different populations, sting frequency and sensitization rates in warm, southern countries seem to be higher than in countries with a cooler climate3, 4: Studies from Sweden 3 and Denmark 1 showed sensitization rates of 9% and 15% respectively, while a study from Turkey 4 reported that 29% of the general population are sensitized. Similarly, individuals who spend a lot of time outside, such as those who hunt and fish, are prone to repeated stings and therefore have a very high risk of sensitization and venom allergy 6, 7, 8. However, there are few data on the prevalence of sensitization and allergy in these population groups.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, this survey demonstrates that 1) a substantial percentage of VIT-treated patients show a long-term loss of HV tolerance, 2) measurements of HV-specific antibodies do not allow an estimation of the clinical status of continued tolerance, and 3) VIT-treated individuals are affected differently in their daily life by emotional distress depending on whether they experienced a re-sting and whether or not they developed an SR. Our findings of an increased re-sting frequency over time (53.7% in a follow-up period of up to 29 years), and at least one fifth of these (6/29) showing loss of tolerance, together with the data from previous reports, firmly strengthen the recommendation for long-term VIT of HV-allergic patients exhibiting risk factors for developing severe SR, like suffering from cardiovascular disease, asthma, clonal mast cell disorders, severe prior SR, increased age, or/and showing increased probability of being stung again due to bee-keeping, outdoor leisure activities, or professional hymenoptera exposure (e.g., working as a gardener, farmer, forest or construction worker, fruit or pastry seller [ 1 , 8 , 44 , 45 ]). This might also hold true for HV-allergic subjects experiencing psychological or emotional distress when close to hymenoptera, which could have profound impact on behavioral patterns and personal feelings, as revealed by the answers to our questionnaire and by other similar investigations.…”
Section: Discussionmentioning
confidence: 99%